Portuguese version of the Delirium Rating Scale-Revised-98: reliability and validity - Negreiros, Daniel Philippi de; Meleiro, Alexandrina Maria Augusto da Silva; Furlanetto, Letícia M.; Trzepacz, Paula T. (International journal of geriatric psychiatry, 2008)
Objective To assess the validity and the reliability of the Portuguese version of the Delirium Rating Scale‐Revised‐98 (DRS‐R‐98). Methods The scale was translated into Portuguese and back‐translated into English. After assessing its face validity, five diagnostic groups (n = 64; delirium, depression, dementia, schizophrenia and others) were evaluated by two independent researchers blinded to the diagnosis. Diagnosis and severity of delirium as measured by the DRS‐R‐98 were compared to clinical diagnosis, Mini‐Mental State Exam, Confusion Assessment Method, and Clinical Global Impressions scale (CGI). Results Mean and median DRS‐R‐98 total scores significantly distinguished delirium from the other groups (p < 0.001). Inter‐rater reliability (ICC between 0.9 and 1) and internal consistency (α = 0.91) were very high. DRS‐R‐98 severity scores correlated highly with the CGI. Mean DRS‐R‐98 severity scores during delirium differed significantly (p < 0.01) from the post‐treatment values. The area under the curve established by ROC analysis was 0.99 and using the cut‐off value of 20 the scale showed sensitivity and specificity of 92.6% and 94.6%, respectively. Conclusion The Portuguese version of the DRS‐R‐98 is a valid and reliable measure of delirium that distinguishes delirium from other disorders and is sensitive to change in delirium severity, which may be of great value for longitudinal studies. Copyright © 2007 John Wiley & Sons, Ltd.